Evolution and Advancements from Neural Network to Deep Learning - Herath, H.M.M.N. (ASEAN Journal of Educational Research and Technology, 2025)
This systematic literature review explores the recent advancements, applications, and challenges in the field of deep learning. By analyzing a diverse array of primary studies, this review elucidates how deep learning technologies have evolved from simple neural network architectures to complex frameworks capable of transforming various scientific and industrial sectors. Key advancements discussed include significant theoretical developments aimed at enhancing model stability and predictability, the evolution of methodologies to ensure adversarial robustness, and the expansive application of deep learning across different domains such as facial recognition, autonomous navigation, and healthcare. The review also addresses critical challenges faced by the field, including the heavy reliance on large, annotated datasets, the substantial computational demands of advanced models, and the ethical concerns arising from the broader integration of these technologies. The findings suggest that future research should focus on developing more efficient unsupervised and semi-supervised learning techniques, enhancing computational algorithms, and fostering interdisciplinary collaborations to address ethical and practical challenges. This review highlights both the remarkable capabilities and the significant limitations of deep learning, providing insights into its future trajectory in the academic and practical realms.